2022
DOI: 10.3390/nu14071459
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Status and Cardiometabolic Health: Findings from a Representative Survey among Children and Adolescents

Abstract: There is preliminary evidence to suggest a positive association between fluoride exposure and higher blood pressure among children, but population-based biomarker studies are lacking. Thus, data from the 2013/2014 and 2015/2016 cycles of the US-based National Health and Nutrition Examination Survey (NHANES) were analysed to evaluate the association between plasma fluoride concentrations and blood pressure among children and adolescents aged 8 to 19 years. Secondary analyses were carried out on fluoride status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…However, our results align with others who also found no association between lower levels of fluoride. 42 , 43 Unlike Liu et al 44 who identified a significant association of fluoride for girls in Mexico City, our study did not demonstrate sex differences.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…However, our results align with others who also found no association between lower levels of fluoride. 42 , 43 Unlike Liu et al 44 who identified a significant association of fluoride for girls in Mexico City, our study did not demonstrate sex differences.…”
Section: Discussioncontrasting
confidence: 88%
“… 28 In these studies, the risk of elevated BP appears to increase for individuals living in fluorosis-endemic areas. 29 , 40 , 43 , 45 , 46 It may be that the connection of fluoride to high BP is dose-dependent and most individuals in the US fall below the threshold needed to increase BP. Further study is needed to explore if dose dependency is an issue and what levels should trigger action by public health officials.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our study did not observe any associations with other anthropometric factors such as body fat, blood pressure, and waist circumference in pre-pubertal children. This is consistent with a few of the abovementioned cross-sectional studies in children ( Ballantyne et al, 2022 ) but inconsistent with the evidence in adolescents ( Liu et al, 2020 ). Yet, it is noteworthy that both anthropometric markers and biomarker data at year 8, particularly body fat, WC, and cholesterol, shared a positive directionality with dietary fluoride, consistent with our hypothesis that fluoride may induce overall deleterious cardiometabolic effects.…”
Section: Discussionsupporting
confidence: 76%
“…For instance, Liu et al ( Liu et al, 2020 ) observed in Mexican adolescents a cross-sectional association of plasma fluoride and higher levels for several cardiometabolic outcomes (BMI, WC, trunk fat percentage, blood pressure, glucose and insulin), but these associations were observed only in girls and no associations were observed in relation to lipids, unlike in our study in children. Only a few studies examined fluoride exposures and cardiometabolic outcomes in children or infants but these were cross-sectional ( Thippeswamy et al, 2021 ; Liu et al, 2019 ; Wang et al, 2020 ; Bai et al, 2020 ): Ballantyne et al ( Ballantyne et al, 2022 ) reported either null associations between plasma fluoride and blood pressure, anthropometry, lipids, glucose metabolism and inflammation markers, or an inverse association with HbA1c levels. Liu et al ( Liu et al, 2019 ) indicated that urinary fluoride concentrations were associated with higher weight, BMI, and higher odds of overweight and obesity, similar to our findings with dietary fluoride but not with urinary fluoride.…”
Section: Discussionmentioning
confidence: 99%